PENGARUH KEPEMIMPINAN HIJAU DAN PENGELOLAAN SDM TERHADAP INOVASI BERKELANJUTAN DI INDUSTRI BERBASIS GREEN ECONOMY DI SUMATERA UTARA - Rudy Sentosa Rajagukguk, Frederick; Welly Arifin, Indra; Handayani Harahap, Hastuti (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study aims to analyze the influence of green leadership and human resource management (HRM) on green economy-based innovation in sustainable industries in North Sumatra. Using a quantitative approach through Partial Least Squares Structural Equation Modeling (PLS-SEM), data were collected from several environmentally oriented companies. The findings reveal that green leadership has a positive and significant effect on green economy-based innovation, and also significantly influences sustainability-adaptive HRM practices. However, HRM does not have a direct significant effect on green innovation. Nonetheless, HRM plays a significant mediating role in the relationship between green leadership and green economy-based innovation. This research highlights the strategic importance of green leadership and HR functions in driving innovative transformation toward sustainable industrial practices.